2008
DOI: 10.1111/j.1540-8159.2008.01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker Therapy for Early and Late Sinus Node Dysfunction in Orthotopic Heart Transplant Recipients: A Single‐Center Experience

Abstract: Although frequently seen as an early complication of OHT, SND remains a risk throughout the lifetime of OHT recipients. Its mechanism is likely multifactorial, and whether this risk can be mitigated over the long term by newer techniques such as bicaval anastamoses remains to be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Unfortunately, we were unable to determine the interaction between ischemic time and donor and recipient age, as multivariate analyses were not feasible with the small number of cases in this study. We also found no association between late‐onset AV block and acute cellular rejection and CAV, as reported by other studies 6,13 . Hence, although we were unable to identify the mechanism of late‐onset AV block, late‐onset SND and AV block appears unlikely to be related to surgical trauma 13 …”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Unfortunately, we were unable to determine the interaction between ischemic time and donor and recipient age, as multivariate analyses were not feasible with the small number of cases in this study. We also found no association between late‐onset AV block and acute cellular rejection and CAV, as reported by other studies 6,13 . Hence, although we were unable to identify the mechanism of late‐onset AV block, late‐onset SND and AV block appears unlikely to be related to surgical trauma 13 …”
Section: Discussionsupporting
confidence: 77%
“…Some studies suggested late‐onset SND and others AV block as the dominant indication for permanent pacing, although the number of patients were generally small (Table III). 4 , 7–11 , 13–16 This study, with 27 patients who required permanent pacing >3 months from heart transplant (13 [48.2%] due to SND and 14 [51.8%] due to AV block) add to these previous reports and suggest that both SND and AV block may contribute equally to the need for permanent pacing late after heart transplantation.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…It is interesting to note that most patients developing SND required their pacemaker within the first 80 days (104 patients, 88%) while only 14 patients required pacemakers later. Luebbert et al presented data showing that in their post‐transplant SND cohort, 58% of the patients required a pacemaker within the first 30 days—in our study, 54% of the patients had received their pacemaker for post‐transplant SND within the first 30 days. A graphical representation of the time of pacemaker implantation in our cohort is shown in Figure .…”
Section: Discussionmentioning
confidence: 46%